Implementasi UU ITE terhadap Pelaku Perjudian Online di Bukittinggi: Analisis Siyasah Tanfidziyah (Studi Kasus Polresta Bukittinggi) - Hengki Januardi; Irfan Perdana Putra; Ramza Fatria Maulana; Aisyah Chairil; Hasanatul Wahida (Al-'Adl, 2026)
The background of this research is motivated by the rise of cybercrime, particularly the increasingly alarming practice of online gambling in Bukittinggi City, along with the rapid development of social media and digitalization of information. The main issues raised in this study are how the implementation of Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE) addresses online gambling in Bukittinggi and how its execution is reviewed from the perspective of siyasah tanfidziyah. The novelty of the research lies in the implementative analysis of the ITE Law through a siyasah approach in the context of local law enforcement. This study employs a qualitative method with a field approach, where data were collected through interviews, observation, and documentation, focusing on the Bukittinggi Police Resort (Polresta Bukittinggi). The results show that the implementation of the ITE Law in Bukittinggi is a progressive step in strengthening digital protection, although it still faces institutional obstacles, human resource limitations, and weak cross-sector coordination. From the perspective of siyasah tanfidziyah, law enforcement demonstrates an orientation toward public welfare through governance and institutional synergy based on Islamic justice values